Mental health services designed for Black, Asian and Minority Ethnics (BAME) in the UK: a scoping review of case studies. Issue 2 (24th January 2020) - Vahdaninia, Mariam; Simkhada, Bibha; van Teijlingen, Edwin; Blunt, Hannah; Mercel-Sanca, Alan
Abstract : Purpose: Mental health disparities exist among Black, Asian and Minority Ethnics (BAME) populations. This paper aims to provide an overview of mental health services designed for the BAME population in the UK, both established BAME communities and refugee/asylum-seekers. Design/methodology/approach: A range of electronic databases were searched for peer-reviewed studies conducted within the past decade in the UK. Using the Arksey and O'Malley methodology, data were extracted, analysed and summarised. Findings: A total of 13 papers were identified, mostly non-randomised community-based. Studies were very heterogeneous in terms of their sample and service provided. After the initial appraisal, the authors presented a narrative synthesis. Overall, all studies reported positive mental health outcomes and beneficial effects. Research limitations/implications: Because of the time limitations and quality of the papers, the authors only included peer-reviewed journal papers. Practical implications: Mental health services provided for BAME people, both established and refugee/asylum-seekers are feasible and improve engagement with the services and mental health outcomes. Initiatives are required to facilitate the integration of these targeted services within mental health and community services for BAME in the UK. Originality/value: This scoping review is a snapshot of the mental health services designed for BAME people in the UK, either established or refugee/asylum-seekers in the past 10 years and adds to the evidence-based knowledge from these studies.